Nation-cultural aspects of scientific communication - Govorushko, S.M. (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
The objective of this publication is to find out how the scientists of different countries and specialties feel about the problems of colleagues. The material was acquired on the basis of analysis of a great number of letters (more than 10 thousand ones to 2542 researchers from 83 countries) containing the different requests. Depending on the result, each answering letter was estimated by a certain score (grade). Further, the scores (grades) were summed for each country and each specialty, the corresponding mean score was determined and the ranking was carried out. The results showed the existence of large differences in response of respondents of different countries. To some extent, the â€œresponseâ€ of countries follows the geographic zonality. As a whole, the lower percentage of positive answers corresponds to decrease in the latitude in the Northern hemisphere. To the contrary, the relation between the specialties of respondents and number of positive answers is practically absent.